Characterization and Application of Activated Carbon from Palm Oil Fuel Ash (POFA) Activated with H₃PO₄ for Surfactant Adsorption in Household Laundry Waste: Review Article - Shofie Chandra Ningtyas; Glen Laura Situmorang; Hadistya Suryadri; Rara Ayu Lestary; Rosmawati Sipayung (Program studi Teknik Kimia UNS, 2026)
ABSTRACT. The rapid growth of laundry businesses has increased the generation of wastewater containing surfactants, particularly Linear Alkyl Benzene Sulfonate (LAS), which can negatively affect aquatic ecosystems if discharged without proper treatment. Adsorption is considered one of the most effective and economical methods for surfactant removal. Palm Oil Fuel Ash (POFA), a by-product of the palm oil industry with high silica content, has attracted attention as a potential precursor for activated carbon. However, studies discussing the characteristics and adsorption performance of H₃PO₄-activated POFA for surfactant removal from household laundry wastewater remain limited and scattered. This review was conducted by analyzing 30 national and international publications published between 2021 and 2025, collected from Google Scholar, ScienceDirect, and other scientific databases using keywords related to POFA, H₃PO₄ activation, surfactants, and adsorbents. The reviewed literature shows that H₃PO₄ activation significantly improves the physicochemical properties of POFA by increasing surface area and pore volume, introducing active functional groups, and enhancing its amorphous structure. Characterization through BET, FTIR, and XRD analyses confirms its suitability as an adsorbent. Previous studies also reported high removal efficiencies for surfactants, COD, BOD, phosphates, and heavy metals, indicating the effectiveness of activated carbon-based adsorption processes. In conclusion, H₃PO₄-activated POFA has strong potential as an environmentally friendly and value-added adsorbent for laundry wastewater treatment. Further experimental studies are required to optimize activation conditions and evaluate adsorption performance under practical operating conditions.Keywords: Palm oil fuel ash (pofa), H₃PO₄ activator, Surfactant, Laundry waste, Environmentally friendly adsorbent